Treatment and final disposal of industrial waste generated in a refinery - Espinoza Eche, José Jorge (2003)
The objective of this article is to establish a methodology for evaluating the current situation of solid and semi-solid waste disposal in a refinery, considering that the problem is common in all of them, as well as establishing alternative solutions to the problem of handling this waste. . To do this, firstly, the work methodology used is described, which is framed in two major blocks: field work and cabinet work. Secondly, the specific topic is developed, focusing the topic on that related to oil sludge and sludge, and evaluating the applicability of the different treatment options, having as a selection framework that option that allows the maximum recycling of waste and minimizes generation of waste and incur the lowest cost of treatment. As conclusions, it is obtained that it is possible to use preconditioned oil slurry and sludge, in use as industrial fuel (in brick kilns, for example) or in use as asphalt on roads or highways; likewise, that the application of only one of the treatment technologies is not sufficient to completely treat the waste from a refinery; and that the selected alternative will depend on a technical economic and environmental analysis.